Optimalisasi Keterampilan Menulis Teks Pidato Melalui Pendekatan Pemberian Tugas di SMP - Nurharyanti, Farida (Muhammadiyah University Press, 2015)
This research aim to description about improvement of achievement of matter learning skill reads textbook through giving approach of duty. Subject and research data source 20 students. Data collecting method applies observation, documentation, and test. Data analysis applies critical analysis and comparability. Indicator success of using minimal limit criteria 75 and complete target of 100%. Research procedure applies cycle. Result of research and solution as follows : data obtained from finite precycle of cycle II, obtained progress of achievement of student learning in study of Indonesian with matter skill reads textbook, at precycle average of 71,7 and cycle I average of 75,1 and cycle II average of 85,1. From this data, seems to explain that happened increase of average of value from precycle to cycle I 3,4 numbers (4,7%), from cycle I to cycle II happened increase 10 numbers (13,3%), from precycle to cycle II happened increase 13,4 numbers (18,7%). Highest value of phase precycle 82 and cycle I 86 and cycle II 92. Seems to explain that from phase precycle to cycle I happened increase equal to 4 number (4,9%), from cycle I to cycle II happened increase equal to 6 number (7%), and from precycle to cycle II happened increase 10 numbers (12,2%). Low value of phase precycle is obtained [by] 64 and cycle I 68 and cycle II 76. thereby, can be affirmed that from phase precycle to cycle I happened increase equal to 4 number (6,3%), from cycle I to cycle II happened increase equal to 8 number (11,8%), and from precycle to cycle II happened increase 12 numbers (18,8%). Complete percentage learnt starts from precycle is obtained equal to25% and cycle I is obtained equal to 50% and cycle II equal to 100%. Seems to explainthat from phase precycle to cycle I happened increase equal to 25%, from cycle I to cycle IIhappened increase equal to 50%, and from precycle to cycle II happened increase equal to75%. Thereby, achievement of student learning in study of Indonesian with matter skill reads textbook from finite precycle of cycle II happened increase significant.